Communication-radar coexistence design based on block diagonalization - Kaifeng HAN; Litao HUANG; Li CHEN; Zhiqin WANG (Tongxin xuebao)
Aiming at the problem of coexistence of communication and radar at the same frequency， a block diagonalization design scheme was proposed.Firstly， an optimization problem was established to maximum the communication system’s sum rate subject to no interference at the radar side and the power budget.To solve this problem， the constraint that the interference between communication users is zero was introduced， so that the non-convex original problem could have a closed-form solution.Then， based on the restriction on the number of base station’s transmit antennas caused by introducing the constraint， two other algorithms were proposed to further consider the block diagonalization design when the constraint was not met.The simulation results show that the proposed algorithms can introduce the constraint to solve the original problem in various scenarios with relative-low computation complexity， which can be implemented in practice.